2016
DOI: 10.3389/fmicb.2016.00981
|View full text |Cite
|
Sign up to set email alerts
|

Produce from Africa’s Gardens: Potential for Leafy Vegetable and Fruit Fermentations

Abstract: A rich variety of indigenous fruits and vegetables grow in Africa, which contribute to the nutrition and health of Africa’s populations. Fruits and vegetables have high moisture and are thus inherently prone to accelerated spoilage. Food fermentation still plays a major role in combating food spoilage and foodborne diseases that are prevalent in many of Africa’s resource disadvantaged regions. Lactic acid fermentation is probably the oldest and best-accepted food processing method among the African people, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 92 publications
(105 reference statements)
1
45
0
Order By: Relevance
“…S. scabrum leaves contained mainly non-acylated quercetin glycosides, such as quercetin-3-neohesperidoside-7-glucosylrhamnoside (isomers), quercetin-3-rutinoside-7rhamnosylglucoside, quercetin-3-galactorhamnoside, quercetin-3-rhamnosylgalactoside, quercetin-3-pentosylglucoside, and quercetin-3-pentosylrutinoside 28 African traditional leafy vegetables are rich in vitamin A and meet more than 75% of the recommended dietary allowance (RDA) (15). The vitamin A content in African nightshade (422 µg retinol activity equivalent, RAE) is greater than that in Jew's mallow (329 µg RAE), pumpkin leaves (325 µg RAE), and tsamma melon leaves (375 µg RAE) (15,32).…”
Section: Composition Of Phytochemical Components In Different Africanmentioning
confidence: 99%
See 1 more Smart Citation
“…S. scabrum leaves contained mainly non-acylated quercetin glycosides, such as quercetin-3-neohesperidoside-7-glucosylrhamnoside (isomers), quercetin-3-rutinoside-7rhamnosylglucoside, quercetin-3-galactorhamnoside, quercetin-3-rhamnosylgalactoside, quercetin-3-pentosylglucoside, and quercetin-3-pentosylrutinoside 28 African traditional leafy vegetables are rich in vitamin A and meet more than 75% of the recommended dietary allowance (RDA) (15). The vitamin A content in African nightshade (422 µg retinol activity equivalent, RAE) is greater than that in Jew's mallow (329 µg RAE), pumpkin leaves (325 µg RAE), and tsamma melon leaves (375 µg RAE) (15,32).…”
Section: Composition Of Phytochemical Components In Different Africanmentioning
confidence: 99%
“…Likewise, fermentation of African kale leaves (B. carinata) with L. plantarum BFE 5092 and Lactobacillus fermentum BFE 6620 starter strains inhibited the growth of L. monocytogenes, S. Enteritidis, and other enterobacteria, while maintaining appreciably the concentration of vitamin C (35 mg 100 g −1 ) in the fermented product (32). Oguntoyinbo et al (32) demonstrated that controlled fermentation is a promising method to reduce food spoilage and extend shelf life and food safety. Fermentation of African nightshade S. scabrum, using 3% salt-sugar solution with L. plantarum BFE 5092 and L. fermentum BFE 6620 as starter cultures, had a greater impact on the microbial profile of the fermented product due to the rapid and stable decline of pH and production of lactic acid (52).…”
Section: Fermentation-a Traditional Food Processing Techniquementioning
confidence: 99%
“…Generally, the consumption of nightshade leaves is in fresh form after cooking, but they have a limited shelf life due to their highly perishable nature. Traditional methods of preserving these indigenous vegetables includes fermentation [2]. Lactic acid bacteria (LAB) are a group of gram-positive bacteria that convert sugars in food into lactic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Amaranth leaves are considered as one of the principal leafy vegetables in tropical areas with high annual production [15]. However, they are mainly used as salads and sauces by adults in most areas [16].…”
Section: Introductionmentioning
confidence: 99%